Odpowiedź :
Odpowiedź i szczegółowe wyjaśnienie:
[tex]\dfrac{4x-3}{3}-\dfrac{6}{1+2x}=0\\\\\dfrac{4x-3}{3}=\dfrac{6}{1+2x}\\\\(4x-3)(1+2x)=3\cdot6\\\\4x+8x^2-3-6x=18\\\\8x^2-2x-3-18=0\\\\8x^2-2x-21=0\\\\a=8;\ b=-2;\ c=-21\\\Delta=b^2-4ac\\\Delta=(-2)^2-4\cdot8\cdot(-21)=4+32\cdot21=4+672=676\\\sqrt\Delta=26\\\\x_1=\dfrac{-b-\sqrt\Delta}{2a}=\dfrac{-(-2)-26}{2\cdot8}=\dfrac{-2-26}{16}=\dfrac{-26}{16}=\dfrac{-8\cdot3}{8\cdot2}=-\dfrac32\\\\[/tex]
[tex]x_1=\dfrac{-b+\sqrt\Delta}{2a}=\dfrac{-(-2)+26}{2\cdot8}=\dfrac{2+26}{16}=\dfrac{28}{16}=\dfrac{7\cdot4}{4\cdot4}=\dfrac74[/tex]